The Educational Upgrading of Japanese Youth, 1982-2007: Are All Japanese Youth Ready for Structural Reforms? - Yoichi Arai; Hidehiko Ichimura; Daiji Kawaguchi (Institute for the Study of Labor (IZA), 2015)
Are all Japanese youth ready for the structural reforms proposed as a supply-side policy of Abenomics? To answer this question, we assess how well Japanese youth have coped with the labor market's long-term structural changes, induced primarily by deepening interdependence with emerging economies and rapid technological progress over the last three decades. We examine the role of educational upgrading on the labor-market outcomes of youth between the ages of 25 and 29, using six waves of micro data from the Employment Status Survey spanning from 1982 to 2007. The analysis demonstrates that the demand growth for skilled labor relative to unskilled labor has been met by the educational upgrading of youth through the expansion of tertiary education, including education in vocational schools. Youth left behind the trend of educational upgrading, however, have suffered significantly from decreasing employment opportunities and deteriorating working conditions.
Keywords: I23; J21; 330; tertiary education; youth employment; Japan